Consistent individual positions within roosts in Spix’s disc-winged bats - Giacomini, Giada (2023)
Individuals within both moving and stationary groups arrange themselves in a predictable manner; for example, some individuals are consistently found at the front of the group or in the periphery and others in the center. Each position may be associated with various costs, such as greater exposure to predators, and benefits, such as preferential access to food. In social bats, we would expect a similar consistent arrangement for groups at roost-sites, which is where these mammals spend the largest portion of their lives. Here we study the relative position of individuals within a roost-site and establish if sex, age, and vocal behavior are associated with a given position. We focus on the highly cohesive and mobile social groups found in Spix’s disc-winged bats (Thyroptera tricolor) given this species’ use of a tubular roosting structure that forces individuals to be arranged linearly within its internal space. We obtained high scores for linearity measures, particularly for the top and bottom positions, indicating that bats position themselves in a predictable way despite constant roost-switching. We also found that sex and age were associated with the use of certain positions within the roost; for example, males and subadults tend to occupy the top part (near the roost’s entrance) more often than expected by chance. Our results demonstrate, for the first time, that bats are capable of maintaining a consistent and predictable position within their roosts despite having to relocate daily, and that there is a link between individual traits and position preferences.